The process of resocialization of former indetainers participating in social projects in Brazil (Research, Society and Development, 2021)
From an initial reading, it can be inferred that former inmates have better opportunities from Social Resocialization Projects, which can bring even more benefits when there is the work of a psychologist, both for the revitalization of the humanization of these women, as in the gathering of relevant information, so that they have better living conditions when they leave the penitentiaries. The research has a bibliographic procedure and a qualitative approach. The data survey was done from the platforms Pepsic, Scielo, Institutional Sites, besides the Sites of the Federal Supreme Court and the Regional Council of Psychology of São Paulo; Resolutions extracted from the Court of Justice of Amazonas, besides materials collected from the library of the University Center FAMETRO. For this fact, the objective of this study is to raise reflections on what resocialization is, besides discussing the labor market and the social prejudice suffered by these women, showing the importance of Brazilian social projects of resocialization, the role of the psychologist and his importance in these projects. For this fact, the results raised were that because these women receive the support and assistance they need, in addition to receiving opportunities that they might not have found otherwise, such as the courses made available, these projects help, in a certain way, these women to get back to a dignified life. Therefore, within this context, other issues to be addressed are the importance of these projects with women still in prison and the statistical survey of the benefits that these projects can bring.